2020
DOI: 10.3390/cancers12082189
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Zfra4-10 or WWOX7-21 Peptide Induces Complex Formation of WWOX with Selective Protein Targets in Organs that Leads to Cancer Suppression and Spleen Cytotoxic Memory Z Cell Activation In Vivo

Abstract: Synthetic Zfra4-10 and WWOX7-21 peptides strongly suppress cancer growth in vivo. Hypothetically, Zfra4-10 binds to the membrane Hyal-2 of spleen Z cells and activates the Hyal-2/WWOX/SMAD4 signaling for cytotoxic Z cell activation to kill cancer cells. Stimulation of membrane WWOX in the signaling complex by a WWOX epitope peptide, WWOX7-21, is likely to activate the signaling. Here, mice receiving Zfra4-10 or WWOX7-21 peptide alone exhibited an increased binding of endogenous tumor suppressor WWOX with ERK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(90 citation statements)
references
References 59 publications
0
90
0
Order By: Relevance
“…pS14-WWOX is expressed in the B16F10 cells infiltrated into this organ, and the injection of Zfra via tail veins prevents B16F10 cells from metastasizing and inhibits the phosphorylation of WWOX on its serine 14 [ 109 , 110 ]. Additionally, the injection of pS14-WWOX7-21 peptide promotes B16F10 cell growth [ 52 , 53 ]. The pS14-WWOX7-21 peptide blocks, while pS14-WWOX antiserum promotes, ceritinib-mediated 4T1 breast cancer stem cells apoptosis [ 53 ].…”
Section: The Function Of Wwox In Cancer Development Is Regulated By Its Phosphorylation Statementioning
confidence: 99%
See 1 more Smart Citation
“…pS14-WWOX is expressed in the B16F10 cells infiltrated into this organ, and the injection of Zfra via tail veins prevents B16F10 cells from metastasizing and inhibits the phosphorylation of WWOX on its serine 14 [ 109 , 110 ]. Additionally, the injection of pS14-WWOX7-21 peptide promotes B16F10 cell growth [ 52 , 53 ]. The pS14-WWOX7-21 peptide blocks, while pS14-WWOX antiserum promotes, ceritinib-mediated 4T1 breast cancer stem cells apoptosis [ 53 ].…”
Section: The Function Of Wwox In Cancer Development Is Regulated By Its Phosphorylation Statementioning
confidence: 99%
“…Fourth, Chang et al reported that different peptides of WWOX (WWOX286-299, WWOX7-21, and WWOX7-11) injected into the tail vein of mice inhibit the growth of melanoma B16F12 cells inoculated into the flanks, revealing their potential use in anticancer treatments [ 52 , 53 ]. Additionally, the WWOX7-21 peptide promotes ceritinib-mediated 4T1 breast-cancer stem cells apoptosis [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in these pathways due to WWOX dysfunction may facilitate disease progression 7 13 . Aberrant WWOX phosphorylation also enhances the progression of cancer and Alzheimer’s disease (AD) 9 , 14 16 . For example, transition of proapoptotic pY33-WWOX to prosurvival pS14-WWOX promotes the progression of both cancer 15 , 16 and AD 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant WWOX phosphorylation also enhances the progression of cancer and Alzheimer’s disease (AD) 9 , 14 16 . For example, transition of proapoptotic pY33-WWOX to prosurvival pS14-WWOX promotes the progression of both cancer 15 , 16 and AD 17 . Human newborns deficient in WWOX suffer severe neural diseases, metabolic disorders, and early death, but fail to form tumors spontaneously 14 , 18 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation